SEPARATION OF WASTE AMINE - BORHAN, MOHAMAD HILMY (universiti teknologi petronas, 2005)
The objectives of this research project are toi l-Demonstrate the separation of mixture ofwaste amines through 2 types of membrane systems. RO and UF 2-Investigate the effect ofpressures different, on the separation of waste amines. 3-Compare the finding of the research with the other literatures.